A Qualitative Study of Nursing Student and Faculty Perceptions of Attrition - Corker, Theresa T.; Kupczynski, Lori; Groff, Shannon L. (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2021)
Institutions of higher learning struggle to supply enough Registered Nursing Professionals to meet demands in today’s healthcare environment. Hundreds of thousands of students are accepted into nursing programs each year, though many fall short of program completion. High attrition and low retention in registered nursing programs is a problem. The purpose of this qualitative study was to evaluate attrition and retention of registered nursing students over a four-year period at a Technical College in Georgia to determine factors impacting successful completion of the Associate of Science in Nursing Program (ASN). It further proposed to identify possible solutions to reduce attrition among nursing students. This study analyzed nursing student and nursing faculty perceptions on the causes of high attrition and low retention and perceived solutions to attrition rates. This study provides insight in the development of steps to decrease attrition in registered nursing programs, and other higher education programs of study.